2020
DOI: 10.3389/fcell.2020.00314
|View full text |Cite
|
Sign up to set email alerts
|

CD95 Structure, Aggregation and Cell Signaling

Abstract: CD95 is a pre-ligand-associated transmembrane (TM) receptor. The interaction with its ligand CD95L brings to a next level its aggregation and triggers different signaling pathways, leading to cell motility, differentiation or cell death. This diversity of biological responses associated with a unique receptor devoid of enzymatic property raises the question of whether different ligands exist, or whether the fine-tuned control of CD95 aggregation and conformation, its distribution within certain plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 101 publications
0
27
0
Order By: Relevance
“…The non-apoptotic pathways that utilise Fas activating signals are, in general, poorly understood, despite evidence about the cell-death independent activities of the Fas/FasL complex accumulating [ 5 , 46 , 47 , 48 , 49 ]. The possible downstream mechanism triggering FasL signalling towards the apoptotic vs. the non-apoptotic fate is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-apoptotic pathways that utilise Fas activating signals are, in general, poorly understood, despite evidence about the cell-death independent activities of the Fas/FasL complex accumulating [ 5 , 46 , 47 , 48 , 49 ]. The possible downstream mechanism triggering FasL signalling towards the apoptotic vs. the non-apoptotic fate is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The possible downstream mechanism triggering FasL signalling towards the apoptotic vs. the non-apoptotic fate is not known. The Fas receptor has no enzymatic activity; therefore, mechanisms such as fine-tuned control of its aggregation/conformation, post-translational modifications, or changes in the distribution pattern within the membrane are being considered [ 48 , 49 ]. Interference with NF-kB signalling is another option; however, the data are still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is also possible that sFasL plays a more active role in immunomodulation. Studies from Legembre and colleagues have shown that naturally cleaved sFasL can engage Fas and activate a PLCg1→PI3K→Akt pathway associated with cell survival, induction of T cell motility, and tumor invasion 80,92,156,157 . To what extent sFasL actively regulates the inflammatory process in glaucoma and other ocular disorders remains an area of active investigation that has important implications for therapeutic applications of sFasL.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The control of the potentially limitless expansion of activated T cells is primarily achieved by activation of the death receptor Fas (CD95/Apo-1) [ 7 ]. Fas is a cell surface glycoprotein that triggers apoptosis upon binding to its cognate ligand, Fas Ligand (FasL/CD95L), or when experimentally activated by specific agonistic antibodies [ 8 ]. Excessive Fas/FasL-mediated apoptosis resulting from abnormal activation and proliferation of T cells has a negative impact in the surrounding tissues, leading to immune-mediated injury.…”
Section: Introductionmentioning
confidence: 99%